The relationship between inflation expectations and consumption in exceptional times: Evidence from Thailand and Vietnam during the Covid-19 Pandemic - Dzung Bui; Bernd Hayo (Philipps-University Marburg, School of Business and Economics, 2024)
Using representative household surveys conducted during the COVID-19 pandemic in two emerging economies, Thailand and Vietnam, we examine the relationship between inflation expectations and consumption. In both countries, our results show an insignificant relationship between expected inflation and durable consumption intentions. In addition, we rigorously test whether the null overall effect of inflation expectations on consumption is due to heterogeneity across different groups of households. However, we cannot reject the homogeneity restriction and conclude that we find no evidence to support either the widely accepted intertemporal optimisation theory or the competing 'stagflationary' view of consumption.
Keywords: E62; E71; D12; D83; H31; 330; Inflation Expectation; Consumption; COVID-19; Thailand; Vietnam